Simple hydrothermal synthesis method for tailoring the physicochemical properties of ZnO: Morphology, surface area and polarity - Cecilia Mateos-Pedrero (2014)
A simple urea-assisted hydrothermal synthesis method was used to tailor the physicochemical properties ofZnO materials. The role of Pluronic P123 block copolymer in the crystal growth, morphology and specificsurface area of the as-prepared ZnO was studied. When Pluronic P123 is used, well-dispersed hierarchicalmicrospheres, with a flower-like morphology, are obtained, but in its absence large spherical agglomeratedclusters are formed. The polarity of the ZnO, measured as the ratio between plane (002) and plane (100), isalso significantly higher for the Pluronic P123 sample. The influence of zinc salt precursors was alsoanalysed. The use of zinc nitrate led to the formation of urchin-like ZnO structures, instead of themicroflowers that result from zinc acetate salt. Despite having similar surface areas, the polarity of thezinc nitrate sample was much smaller. The decomposition of methylene blue corroborated the higherphotocatalytic activity of the ZnO materials with a higher proportion of polar planes (higher polarity). Theformation mechanism of the crystals is also suggested based on the observed gradual growth andassembly of the hydrozincite during the initial steps of the synthesis for the samples with and withoutPluronic P123.